Aplicación de la mediación penal como mecanismo alternativo de solución de conflictos en adolescentes infractores, en el cantón Cayambe en el año 2019. - Charro, Verónica E. (2022)
The investigation seeks to analyze criminal mediation as an alternative conflict resolution mechanism in the judicial processes of adolescent offenders in the Cayambe canton during the year 2019, due to bureaucratic obstacles, judicial congestion, which cause there to be a minimum of cases in the country that comes to trial and sentencing, which causes the frustration of the victims, the discredit of justice and impunity in the face of crime. Given these facts, mediation is the administrative support mechanism that allows us to be agile, efficient, and effective in solving this problem; for which the present study based the criminal procedure system and mediation, I determine the principles and criminal procedure guarantees so that through mediation the adolescent is reinserted into society and finally the analysis of the cases submitted to the application of the measurement penal. The instruments used for this investigation were the questionnaire and the analysis of statistical data, the results of which were applied to judges, prosecutors, defenders and lawyers in free practice with a sample of 42 people, who demonstrated that mediation has been applied to cases of material damage, for theft and robbery currently, but it is necessary to create Follow-up Units for the treatment of adolescent offenders to guarantee the reintegration of adolescents into society. With regard to statistics, it is noted that mediation had an increase in application between 2016 and 2017, maintaining similar data until 2019. The following data due to the effects of the COVID-19 pandemic have not been updated as they were obtained from the National Center for Mediation of the Judicial Function.